Recycling Sampah Plastik Menjadi Produk Bernilai Jual - Hulaikah, Mifta (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
The use of food wrap made of plastic is very popular because plastic is lightweight, easy to carry and of course the price is affordable. This results in a lot of plastic waste. One way to reduce it is with the 3R program (reuse, reduce, recycle). In addition, the problem experienced by the community is that plastic waste is not utilized as a selling value product so that it is expected to increase side income for housewives. This service aims to provide training on recycling plastic waste into products that are worth selling.